1991
DOI: 10.1007/bf00846175
|View full text |Cite
|
Sign up to set email alerts
|

Resting heart rate (HR) in women with and without premenstrual symptoms (PMS)

Abstract: A sample of 64 undergraduate female students participated in the present experiment. During 3 consecutive months women answered a chart of daily report of symptoms, and finally, two groups were formed: women with premenstrual symptoms (PMS group) and women without premenstrual symptoms (NPMS group). Heart rates (HR) at rest were recorded throughout premenstrual, menstrual, postmenstrual, and ovulatory phases. In the premenstrual phase, PMS group showed significantly higher resting HR levels than NPMS group. Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
0
7
0
1
Order By: Relevance
“…A study of 64 undergraduate women showed an increase in resting heart rate in those who experience PMS. 46 Nutrition, chiropractic adjustments, and medications are methods used to combat the symptoms of PMS. Nutritional supplementation with calcium carbonate (1200 mg/d) reduced the symptoms of PMS for some women.…”
Section: Dysmenorrhea and Pmsmentioning
confidence: 99%
“…A study of 64 undergraduate women showed an increase in resting heart rate in those who experience PMS. 46 Nutrition, chiropractic adjustments, and medications are methods used to combat the symptoms of PMS. Nutritional supplementation with calcium carbonate (1200 mg/d) reduced the symptoms of PMS for some women.…”
Section: Dysmenorrhea and Pmsmentioning
confidence: 99%
“…Girdler et al (3) reported that women with PMDD had greater norepinephrine levels than control women both while quietly resting, and when under experimental stress conditions, regardless of menstrual phase, suggesting greater sympathetic nervous system (SNS) activity in the PMDD women. One study (4) reported that women with PMS have a higher resting heart rate than controls in the late-luteal phase, consistent with altered autonomic nervous system function, but others have failed to replicate this effect (5,6). Measures of skin conductance, used as an index of sympathetic tone, have also produced conflicting results, with some studies reporting greater skin conductance in women with PMS (7), others reporting no difference between women with PMS and controls (8), and yet others reporting higher levels of skin conductance pre-menses than post-menses in women with PMS, an effect opposite to that seen in controls (9).…”
Section: Introductionmentioning
confidence: 99%
“…5 The heart rate variability was significantly higher in the luteal phase compared to the follicular phase, suggesting increased sympathetic activity in the luteal phase; the alteration in the balance of ovarian hormones might be responsible for these changes in the cardiac autonomic innervations. 6 The plasma norepinephrine levels were significantly higher in the mid-luteal phase than in the early follicular phase; therefore the hormonal fluctuations that occur during the normal menstrual cycle may alter sympathetic outflow.…”
Section: Discussionmentioning
confidence: 99%